2021
DOI: 10.1021/acsmacrolett.0c00724
|View full text |Cite
|
Sign up to set email alerts
|

100th Anniversary of Macromolecular Science Viewpoint: Solid Polymer Electrolytes in Cathode Electrodes for Lithium Batteries. Current Challenges and Future Opportunities

Abstract: Solid polymer electrolytes (SPEs) are an important class of ion-transporting materials for enabling safe and highenergy-density all-solid lithium batteries. Within the composite cathode electrode (CCE), an SPE plays a critical role as both binder material for mechanical integrity and electrolyte to facilitate ion transport. The inclusion of an SPE within the CCE leads to the formation of distinctive heterogeneous SPE/solid interfaces that are not present in traditional liquid electrolyte-containing CCE.Here, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 101 publications
0
22
0
Order By: Relevance
“…The principal strategies of increasing SPE’s anodic stability include modifying the SPE chemical structure or introducing small molecular additives. Studies have shown that poly­(sulfone) (PSU)-based and PAN-based polymers can be stable to over 5 V. However, the rigidity of the chains and high glass transition temperature (PSU ∼ 185 °C, PAN ∼ 95 °C) hinder ion transport and undermine an otherwise conformal coating layer between the SPE and the electrode. , Recently reported comb-chain cross-linker-based network SPEs showed high oxidative stability . On the other hand, introducing salt additives has already been an effective way to tune properties in the liquid electrolyte field.…”
Section: Introductionmentioning
confidence: 99%
“…The principal strategies of increasing SPE’s anodic stability include modifying the SPE chemical structure or introducing small molecular additives. Studies have shown that poly­(sulfone) (PSU)-based and PAN-based polymers can be stable to over 5 V. However, the rigidity of the chains and high glass transition temperature (PSU ∼ 185 °C, PAN ∼ 95 °C) hinder ion transport and undermine an otherwise conformal coating layer between the SPE and the electrode. , Recently reported comb-chain cross-linker-based network SPEs showed high oxidative stability . On the other hand, introducing salt additives has already been an effective way to tune properties in the liquid electrolyte field.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we build our discussion on the extensive knowledge base already available on batteries with solid polymer and liquid electrolytes as this gives important insight into the CAM polymer interactions and may provide a directive on how polymer coatings can also benet SSBs with ISEs. 13,14,160 Electrochemical stability window of polymer interlayers For application in composite cathodes, polymer coatings should be stable at high potential versus Li + /Li to avoid electrochemical oxidation within the potential range of intercalation-type CAMs. In general, to prevent oxidation (and reduction) of the polymer coating in a battery, the intrinsic electrochemical stability window (ESW) of the polymer should extend beyond the electrochemical potential of the electrodes.…”
Section: Role Of Polymer Interlayers In Cathodementioning
confidence: 99%
“…163 Still, the most used polymer coating is PEO-LiTFSI, as employed with LCO, LFP and NMC cathodes. 84,160,164,165 The ESW of PEO-LiTFSI (3.8 V versus Li + /Li with carbon electrode) limits their application for high voltage cathodes. 166 With LCO and LiNi 0.5 -Mn 1.5 O 4 (LNMO) cathodes, PEO-LiTFSI electrolyte exhibits a noisy voltage prole, which is interpreted as possible decomposition of PEO-LiTFSI in contact with a high voltage cathode.…”
Section: Role Of Polymer Interlayers In Cathodementioning
confidence: 99%
“…Dry solid polymer electrolytes (SPEs) could be a possible solution to the safety issues associated with the use of flammable and toxic liquid electrolytes in commercial Li-ion batteries. Most importantly, SPEs hold the key for the realization of high-energy-density alkali-metal batteries as they can be made chemically stable toward alkali metals, to form a good interface with the metal, while their mechanical resistance could reduce/impede or even suppress, dendrite formation and growth from alkali-metal electrode and eliminate the associated safety hazards and the catastrophic failure of the battery. Despite the considerable research effort in SPEs, the development and realization of their potential have been hampered by the inability to design materials that possess simultaneously high ionic conductivity, good mechanical properties, and cation transference number close to unity (i.e., single-ion solid polymer electrolytes, t Li + = 1). To this end, conventional SPEs are formed by mixing Li salt with a polar polymer host that dissociates the lithium salt and are dual-ion conductors as both the cations and anions are mobile.…”
Section: Introductionmentioning
confidence: 99%